Islāmic Aesthetics: Art and Beauty (Philosophy and Progress, 2022)
Islāmic aesthetic is an outcome of Islāmic civilisation based on Islāmic metaphysics and theology and emphasizes that God is the origin or source of all art and thought, including various art forms. Thus, the essences or forms of all things have their reality in the Divine Wisdom or Intellect (Al-‘Aql-i-Awwal). Islāmic conception of art and beauty has its origin in Islāmic Weltanschauung, so, each object of beauty in nature reflects the Creative and Aesthetic aspect of Jamīl Allāh with His Jamāl. Generally, in Muslim world, art and beauty are almost neglected ones, so, they are not given significant and sufficient importance because of some unauthentic and false notions and consequently, we have almost lost this pristine Islāmic heritage and now we must revisit it and realise its vital function and role in our socio-political and ethico-spiritual life. Islāmic aesthetics has a significant role in the cultural tradition of Islāmic Ummah, so it must be revitalised for a peaceful life’s onward caravan. In the present paper, an effort has been made to discuss the etymological meaning of ‘aesthetics’ in general and the main features of Islāmic conception of aesthetics, including art and beauty, in particular, along with various Islāmic art-forms.Philosophy and Progress, Vol#69-70; No#1-2; Jan-Dec 2021 P 119-144